1997
DOI: 10.1042/bj3220001
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanisms that modulate signalling by G-protein-coupled receptors

Abstract: The large and functionally diverse group of G-protein-coupled receptors includes receptors for many different signalling molecules, including peptide and non-peptide hormones and neurotransmitters, chemokines, prostanoids and proteinases. Their principal function is to transmit information about the extracellular environment to the interior of the cell by interacting with the heterotrimeric G-proteins, and they thereby participate in many aspects of regulation. Cellular responses to agonists of these receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
322
1
7

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(343 citation statements)
references
References 227 publications
(206 reference statements)
10
322
1
7
Order By: Relevance
“…It has been revealed that putative Ser/Thr phosphorylation sites are present in the cytoplasmic tail of PAFR (51). PKC activation can phosphorylate these residues, resulting in the interaction with ␤-arrestin and uncoupling from the G-protein, leading to the desensitization and receptor internalization (52). This may explain the early phase effect of PDB observed in our study, as the inhibition of PAF-triggered [Ca 2ϩ ] i elevation by PDB could be blocked by pretreatment with BIM, a specific PKC inhibitor.…”
Section: Discussionsupporting
confidence: 62%
“…It has been revealed that putative Ser/Thr phosphorylation sites are present in the cytoplasmic tail of PAFR (51). PKC activation can phosphorylate these residues, resulting in the interaction with ␤-arrestin and uncoupling from the G-protein, leading to the desensitization and receptor internalization (52). This may explain the early phase effect of PDB observed in our study, as the inhibition of PAF-triggered [Ca 2ϩ ] i elevation by PDB could be blocked by pretreatment with BIM, a specific PKC inhibitor.…”
Section: Discussionsupporting
confidence: 62%
“…After binding of SDF, CXCR4 is sequestered into early endosomes enabling a rapid recycling of the chemokine receptor after removal of the ligand. In addition to agonistdependent receptor phosphorylation by G-proteincoupled receptor kinases, other kinases like PKC may mediate receptor internalization and desensitization either by directly phosphorylating G-protein-coupled receptors or by the indirect up-regulation of G-proteincoupled receptor kinases [24,25]. For example, rapid internalization of CXCR4 was observed after stimulation of lymphocytes with phorbol esters [14,26].…”
Section: Discussionmentioning
confidence: 99%
“…1a) is reminiscent of short-term receptor desensitization (6,7). Receptor desensitization has been extensively studied in the ␤-adrenergic receptor system (6) and has also been described for opioid receptors mostly in terms of the diminishing agonist inhibition of cAMP levels induced by forskolin (2-4).…”
Section: Resultsmentioning
confidence: 99%
“…Desensitization of the -opioid receptor involves agonistdependent phosphorylation of the receptor, most likely by a member of the family of G-coupled receptor protein kinases (GRKs) (4,5). According to this model, upon phosphorylation and uncoupling from the G protein, the receptor is bound to ␤-arrestins and internalized into endosomes, reducing the number of receptors available at the cell surface for further agonist binding (6,7).…”
mentioning
confidence: 99%